Hypersensitivity Pneumonitis: A Rare Diagnosis - Monteiro Cunha, Sara (2021)
Introduction: Hypersensitivity pneumonitis (HP) is a pulmonary inflammatory disease associated with the exposition of several environmental agents in immunological susceptible individuals. HP is a rare disease and its exact prevalence remains unknown in children. Case report: A healthy ten-year-old male hospitalised with complaints of fatigue, anorexia, abdominal pain, and dry cough. He subsequently developed dyspnoea after mild exertion and episodes of desaturation at rest. Radiological studies and more invasive exams allowed the diagnosis of hypersensitivity pneumonitis of unknown aetiology. Conclusion: The clinical presentation and findings in first-line diagnostic exams are non-specific. Therefore, the diagnosis of HP requires a high index of suspicion. Timely diagnosis is associated with a better prognosis along with an early implementation of corticosteroid therapy and antigen avoidance, if possible.